Seizing the Meaning of "Comprehensive" in Sexuality Education in Indonesia - Rita Hendrawaty Soebagio (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The meaning of comprehensive in sexuality education is frequently associated with the breadth of topics included in the curriculum, although such breadth does not necessarily provide a coherent philosophical foundation for educational practice. This study critically examines how comprehensiveness is conceptualized in sexuality education implemented in Indonesia and reconstructs its meaning through the Islamic concept of kaffah. A qualitative conceptual-critical design was employed, integrating comparative document analysis with empirical evidence obtained from a survey of 227 elementary school teachers, semi-structured interviews with children, parents, teachers, and child–youth mentors, two focus group discussions, and expert validation. The findings reveal conceptual, pedagogical, and systemic limitations within existing sexuality education frameworks. More than half of the participating teachers demonstrated limited conceptual understanding of sexuality education, while classroom practices remained largely fragmented and concentrated on biological aspects. Comparative analysis further indicates that prevailing approaches primarily reflect horizontal comprehensiveness, emphasizing content coverage rather than philosophical integration. In response, this study proposes an Islamic Comprehensive Sexuality Education (PSKI) framework that combines age-appropriate scientific knowledge, child protection, and health literacy with the principles of tawḥīd, fiṭrah, amānah, adab, maqāṣid al-sharīʿah, ḥayāʾ, and ʿiffah. This reconstruction extends current discussions by redefining comprehensiveness as the integration of educational content, ethical orientation, and holistic human development, providing a conceptually grounded framework for curriculum development, teacher preparation, and sexuality education policy in Muslim elementary education.